2020
DOI: 10.1155/2020/8840676
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis of Hydraulic Pumps Using PSO-VMD and Refined Composite Multiscale Fluctuation Dispersion Entropy

Abstract: Multiscale fluctuation dispersion entropy (MFDE) has been proposed to measure the dynamic features of complex signals recently. Compared with multiscale sample entropy (MSE) and multiscale fuzzy entropy (MFE), MFDE has higher calculation efficiency and better performance to extract fault features. However, when conducting multiscale analysis, as the scale factor increases, MFDE will become unstable. To solve this problem, refined composite multiscale fluctuation dispersion entropy (RCMFDE) is proposed and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Along with the emergence of intelligent optimization algorithms, attempts have been made to apply some optimization algorithms in the optimization of VMD parameters, and satisfying results have been obtained [24,29,30]. Zhou et al [31] put forward the particle swarm optimization (PSO) to optimize the VMD parameters. In this method, they used mean permutation entropy (MPE) as its fitness function and determined the optimal combination of K and α by searching for the minimum of the fitness function.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the emergence of intelligent optimization algorithms, attempts have been made to apply some optimization algorithms in the optimization of VMD parameters, and satisfying results have been obtained [24,29,30]. Zhou et al [31] put forward the particle swarm optimization (PSO) to optimize the VMD parameters. In this method, they used mean permutation entropy (MPE) as its fitness function and determined the optimal combination of K and α by searching for the minimum of the fitness function.…”
Section: Introductionmentioning
confidence: 99%
“…To conquer the shortcomings of the coarsening method in the multi-channel signals for MFDE, On the basis of MFDE, GAN et al introduced the coarse-grained method and proposed the composite multi-scale wave dispersion entropy (CMFDE) [ 14 ], proving that the sliding coarse-grained method based on CMFDE has better entropy stability. Zhou et al proposed that refined complex multi-scale fluctuation dispersion entropy (RCMFDE) [ 15 ] is stronger and more stable in extracting features, and RCMDE has a smaller dependence on the length of time series. Azami et al proposed multi-variable multi-scale dispersion entropy (MMDE) [ 16 ] in order to quantify the complexity of multivariate time series.…”
Section: Introductionmentioning
confidence: 99%
“…But in wavelet transform, the choice of wavelet basis has great influence on the result, and there is no adaptive to the local analysis of the signal. Through the research of many scholars, it is found that the most effective way to separate the useful signal from the noisy signal is to apply the idea of signal decomposition [9]- [11], but it is still not easy to extract the weak signal features under the strong noise background, and there are three main difficulties in this regard:  The application scope of the current weak signal feature extraction methods is relatively limited, so it is difficult to find a method that is simultaneously suitable for detecting the signal under nonlinear, unstable and non-Gaussian noise environment.…”
Section: Introductionmentioning
confidence: 99%